Two contrasting views of the South Korea ferry accident: Lessons learned from using a story-based animation for dissemination of research [Abstract] - Gyuchan Thomas Jun; Man Ki Park; Patrick Waterson; Roger Haslam (2016)
Two contrasting views of the South Korea ferry accident: Lessons learned from using a story-based animation for dissemination of research [Abstract]